Still killing us softly advertising's image of women - Lazarus, Margaret (Cambridge : Cambridge Documentary Films, 1987)
Disscused on the exploitation of women in maas media and advertising industry in United States
Speaker: Jean Kllbourne
Keywords: Women in mass media; Women in advertising; Women in the advertising industry